2014
DOI: 10.1162/jocn_a_00633
|View full text |Cite
|
Sign up to set email alerts
|

The Neural Basis of Involuntary Episodic Memories

Abstract: Voluntary episodic memories require an intentional memory search, whereas involuntary episodic memories come to mind spontaneously without conscious effort. Cognitive neuroscience has largely focused on voluntary memory, leaving the neural mechanisms of involuntary memory largely unknown. We hypothesized that because the main difference between voluntary and involuntary memory is the controlled retrieval processes required by the former, there would be greater frontal activity for voluntary than involuntary me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
106
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 104 publications
(120 citation statements)
references
References 62 publications
13
106
1
Order By: Relevance
“…Clearly evident, however, was the effect of retrieval mode upon reaction time, which is consistent with previous findings as well as neuroimaging data demonstrating increased activity in prefrontal regions using a voluntary, compared with involuntary, retrieval mode (Hall et al, 2014). The present study presents behavioural data showing that the retrieval dynamics of involuntary future MTT are highly similar to those of involuntary memories.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Clearly evident, however, was the effect of retrieval mode upon reaction time, which is consistent with previous findings as well as neuroimaging data demonstrating increased activity in prefrontal regions using a voluntary, compared with involuntary, retrieval mode (Hall et al, 2014). The present study presents behavioural data showing that the retrieval dynamics of involuntary future MTT are highly similar to those of involuntary memories.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, involuntary memories are elicited faster than voluntary memories Schlagman & Kvavilashvili, 2008), suggesting that their retrieval is less effortful. Convergent results have been found in neuroimaging, such that, compared with involuntary retrieval, voluntary retrieval is associated with greater activity in brain regions implicated in high-level control processes (Hall et al, 2014). Nevertheless, a common set of neural structures associated with recollection are activated for both voluntary and involuntary episodic memories (Hall et al, 2014).…”
Section: Studies Of Voluntary and Involuntary Memoriesmentioning
confidence: 94%
See 2 more Smart Citations
“…Similarly, it has been found that voluntary episodic memories involve the lateral prefrontal cortex to a greater extent than involuntary episodic memories, with otherwise extensive 14 overlaps in default network activity between the two kinds of memories (Hall et al, 2014).…”
mentioning
confidence: 92%